2019
DOI: 10.5851/kosfa.2019.e22
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Humic Acid and Blueberry Leaf Powder Supplementation in Feeds on the Productivity, Blood and Meat Quality of Finishing Pigs

Abstract: The objective of this study was to determine effects of humic acid (HA) and blueberry leaf powder (BLP) supplementation in pig feed on productivity, blood profiles, and meat quality characteristics of longissimus muscle. The experimental design included six treatments: 1) CON, no addition; 2) T1, BLP 0.1%; 3) T2, BLP 0.2%; 4) T3, humic acid 2%; 5) T4: humic acid 2%+BLP 0.1%; and 6) T5: humic acid 2%+BLP 0.2%. HA and BLP supplementation in pig feed significantly increased average daily fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…Anthocyanins have been reported to alleviate heat stress in chickens, revealing significant effects on growth performance [26]. Studies on effects of blueberry leaf powder on growing pigs productive parameters, showed that body weight or average daily gain were not significantly affected [27]. Studies on chickens have demonstrated the effectiveness of walnut leaves in enhancing growth [28], in contrast with our results where walnut leaves dietary supplements did not improve the productive parameters.…”
Section: Discussioncontrasting
confidence: 98%
“…Anthocyanins have been reported to alleviate heat stress in chickens, revealing significant effects on growth performance [26]. Studies on effects of blueberry leaf powder on growing pigs productive parameters, showed that body weight or average daily gain were not significantly affected [27]. Studies on chickens have demonstrated the effectiveness of walnut leaves in enhancing growth [28], in contrast with our results where walnut leaves dietary supplements did not improve the productive parameters.…”
Section: Discussioncontrasting
confidence: 98%
“…Humic acids and their sodium salts are permitted for oral use (inclusion level: 500−2000 mg/kg of body weight) in horses, ruminants, swine and poultry for the treatment of diarrhoea, dyspepsia and acute intoxications (EGTOP/1/, 2011). Lower levels of humic substances used as a feed additive (2−10 g/100 g of diet) in the pigs' diet seem to demonstrate that they improve growth performance and meat quality, also reducing ammonia emissions from manure (Ji et al, 2006;Wang et al, 2008;Kim et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The color values of stored chicken nuggets decreased during storage which can be ascribed to moisture loss and oxidation of meat proteins Jiang et al (2009). reported that dietary soy isoflavone significantly improved the color of broiler meat Kim et al (2019). reported that dietary interventions of humic acid and blueberry powder in animal diet significantly improved the color values of meat.…”
mentioning
confidence: 99%